Sistem Pendukung Keputusan Pemilihan Duta Bahasa Pelajar Dengan Menggunakan Metode Exprom II (Studi Kasus: Balai Bahasa Sumatera Utara) - Elisabet Simbolon; Mesran Mesran; AM Hatuaon Sihite (STMIK Budi Darma, 2019)
The selection process for Student Language Ambassadors at the North Sumatra Language Hall is still subjective in that the assessment may not be based on established criteria or without looking objectively so the selection process is less precise and the resulting decisions are less satisfactory for the students' Language Ambassador participants. In this study, the authors used a decision support system with the Exprom II method to find the value of weights and criteria, and to find the final grade or to find the value of the Student Language Ambassador ranking. Thus the Decision Support System is needed so that it can help the North Sumatra Language Office in determining Student Language Ambassadors. To overcome these problems, it is necessary to build a decision support system application for selecting Student Language Ambassadors using the Exprom II method so that it can help and facilitate the North Sumatra Language Hall in making decisions choosing Student Language Ambassadors and the decisions determined are satisfactoryKeywords: Decision Support System, Student Language Ambassador, Exprom Method II